From Waste to E-Money: The Role of Village-Owned Enterprise in Community Empowerment in Jember, Indonesia - Selfi Budi Helpiastuti; Julvia Nurlaela Firmawati; Ladiqi, Suyatno (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2024)
This innovative approach not only supports sustainable waste management but aligns with global trends of incentivizing waste management through financial rewards, as seen in countries integrating waste management with the digital economy. By converting waste into electronic money credit, the program addresses waste issues while promoting economic empowerment. A qualitative approach was employed, with data collected through observation, interviews, and documentation. An interactive model was used to analyze how the BUMDes waste management system integrates with the global circular economy framework. The results of the study indicate that BUMDes plays an important role in adopting community-based innovations that not only reduce waste volume but also encourage economic empowerment through financial incentive mechanisms. developing community potential, improving the regional economy, improving the institutional framework, and encouraging environmental sustainability through processing waste into electronic money.